2015
DOI: 10.1057/jit.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Information System Investments: A Value Dials approach to closing the theory-practice gap

Abstract: Failed or partially failed information systems (IS) investments continue to be a problem in both public and private sectors. Although there are many causes of such failure, lack of clarity about the goals and benefits expected and how they are to be realized is one of the major contributors. This is particularly so in the public sector where the purpose of IS investment is not to increase profits, but to accomplish social and political goals. One way of reducing failure and wastage rates is to have ex-ante eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 58 publications
0
20
0
1
Order By: Relevance
“…Selecting the right analytical tool that will meet the requirements of data analysis is vital to ensure return on investment and the added value of the generated information. When developing the best marketing strategy the attention of responsible staff should be shifted from traditional analytical tools to advanced and specialized analytical tools [12]. This is especially important in marketing, where hundreds of potentially relevant metrics need to be considered.…”
Section: Literature Overview a Importance Of Data Analysis In Strategic Planningmentioning
confidence: 99%
“…Selecting the right analytical tool that will meet the requirements of data analysis is vital to ensure return on investment and the added value of the generated information. When developing the best marketing strategy the attention of responsible staff should be shifted from traditional analytical tools to advanced and specialized analytical tools [12]. This is especially important in marketing, where hundreds of potentially relevant metrics need to be considered.…”
Section: Literature Overview a Importance Of Data Analysis In Strategic Planningmentioning
confidence: 99%
“…When reviewing the history of the Information systems (IS) discipline, Hirschheim and Klein (2012) position benefits realisation as an extension of the IT evaluation literature. As pointed out by Frisk, Bannister and Lindgren (2015), the available literature of IT evaluation is extensive and thus too diverse to use as a basis for our research. Rather, we are focusing on one of the specific research streams related to IT evaluation, namely what is commonly referred to as benefits management (BM) or benefits realisation (BR).…”
Section: Related Research 21 Benefits Realisation In Information Systems Researchmentioning
confidence: 99%
“…Despite this, BR approaches have been adopted in practice, where the Benefits management model (BMM) has been the most influential (Mohan, Ahlemann and Braun, 2016;Waring, Casey and Robson, 2018). However, few empirical studies on how the BM process occur in practice can be found (Doherty, 2014;Frisk, Bannister and Lindgren, 2015), especially from public sector (Juell-Skielse, Lönn and Päivärinta, 2017) and inter-organisational collaborations (Lönn, Juell-Skielse and Päivärinta, 2016).…”
Section: Related Research 21 Benefits Realisation In Information Systems Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects in large part the difficulties in conducting effective studies of technological interventions in complex environments, which has generated an extensive literature on Information Systems evaluation approaches over multiple decades in both the public and private sectors. Where effort has been spent on the ex ante evaluation of investment decisions, a focus is possible on stakeholder involvement and both metric‐based and qualitative analysis of the particular problem for which information systems are being proposed to solve (see Frisk, Bannister, & Lindgren, ). The goals and metrics established can then be used after implementation to understand if the investment has achieved its goals.…”
Section: Introductionmentioning
confidence: 99%